2010
DOI: 10.3109/13550280903586394
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the brain during reovirus encephalitis

Abstract: Viral encephalitis remains a significant cause of morbidity and mortality throughout the world. We performed microarray analysis to identify genes and pathways that are differentially regulated during reovirus encephalitis and that may provide novel therapeutic targets for virus-induced diseases of the central nervous system (CNS). An increase in the expression of 130 cellular genes was found in the brains of reovirus-infected mice at early times post infection, compared to mock-infected controls. The up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…1a). The magnitude of Daxx transcript upregulation at 8 days post-T3A infection (5.2-fold over mock; P ϭ 0.003) was comparable to that previously seen 8 days post-T3D infection (4.1-fold over mock; P ϭ 0.000059) by microarray analysis (44).…”
Section: Brain Expression Of Daxx Mrna and Protein Is Upregulated Dursupporting
confidence: 55%
See 2 more Smart Citations
“…1a). The magnitude of Daxx transcript upregulation at 8 days post-T3A infection (5.2-fold over mock; P ϭ 0.003) was comparable to that previously seen 8 days post-T3D infection (4.1-fold over mock; P ϭ 0.000059) by microarray analysis (44).…”
Section: Brain Expression Of Daxx Mrna and Protein Is Upregulated Dursupporting
confidence: 55%
“…Upregulation of Daxx was previously reported in bone marrow cells following type I IFN exposure (46,47). We previously showed that interferon signaling is initiated in the reovirus-infected brain and serves to limit local viral tropism and systemic viral spread (11,40,44). Thus, we hypothesized that IFN was driving Daxx upregulation during reovirus infection.…”
Section: Brain Expression Of Daxx Mrna and Protein Is Upregulated Durmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, (i) Daxx is upregulated in the spleens of mice infected with neuroinvasive strains of WNV compared to noninvasive strains (23); (ii) the death receptor-associated genes encoding cIAP2, TRAIL, TNF, and TRAF1 are upregulated in WNV-infected human retinal pigment epithelium (24), and (iii) multiple pathways involved in apoptosis, including induction of apoptosis by HIV-1, were identified in the brains of horses with exposure to WNV (25). In addition, we previously performed microarray analysis on RNA extracted from the brains of reovirus-infected mice (26). The expression of all DR-associated WNV-induced genes with an expression change of Ն2 was also significantly changed following infection of the brain with reovirus (not shown), including the gene encoding Daxx (27), suggesting that similar patterns of gene expression are seen in the brain following infection with a variety of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of p53 have been shown to promote cell death by transcriptionally activating proapoptotic genes, including Bax and PUMA. Our prior microarray studies indicated that Bax and PUMA are not upregulated in the brain throughout the course of reovirus infection (21), suggesting that the transcriptional activity of p53 does not contribute to pathology during reovirus encephalitis. The cytoplasmic location of p53 ( Fig.…”
Section: Levels Of P53 Are Increased In the Brain Following Reovirus mentioning
confidence: 99%